2020
DOI: 10.1002/jmv.26283
|View full text |Cite
|
Sign up to set email alerts
|

Lineage analysis of human papillomavirus type 18 based on E6 region in cervical samples of Iranian women

Abstract: Distinct human papillomavirus (HPV) 18 variants are thought to differ in oncogenic potential and geographic distribution. As such, understanding the regional variants of HPV 18 would be of great importance for evolutionary, epidemiological, and biological analysis. In this regard, the sequence variations of E6 gene were investigated to characterize more common variants of HPV 18 in normal cells, premalignant, and malignant samples collected from the cervix. In total, 99 samples of HPV 18 were analyzed by polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
3
10
1
Order By: Relevance
“…Although the sample size was small for HPV 18, A3 was the predominant variant, followed by A4. This finding is inconsistent with the results of a study by Salavatiha et al, which reported HPV 18 A4 variant to be predominant in Iran, [ 23 ]. The HPV 18 A1 variants are prevalent in the Asia-Pacific region, and A3 variants account for a large proportion of variants in Europe, Southern/Central Asia, and America [ 7 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although the sample size was small for HPV 18, A3 was the predominant variant, followed by A4. This finding is inconsistent with the results of a study by Salavatiha et al, which reported HPV 18 A4 variant to be predominant in Iran, [ 23 ]. The HPV 18 A1 variants are prevalent in the Asia-Pacific region, and A3 variants account for a large proportion of variants in Europe, Southern/Central Asia, and America [ 7 ].…”
Section: Discussioncontrasting
confidence: 99%
“…There are few studies that characterized the common HPV 16, 18, 31, and 45 lineages/sublineages in Iran. [13][14][15] The PCR products were subjected to sequencing using bidirectional direct sequencing as described above. All sequences of this study were deposited at http://www.ncbi.nlm.nih.gov/.…”
Section: Introductionmentioning
confidence: 99%
“…Although the geographical distribution of HPV types in Iran is identified, there is less data with regard to HPV lineages or sublineages. There are few studies that characterized the common HPV 16, 18, 31, and 45 lineages/sublineages in Iran 13–15 . Therefore, in this study, basic data was provided regarding HPV 56 lineages and sublineages circulating among Iranian women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the spreading of HPV types is identified in Iran, there is much less known about HPV variants. Previous studies were investigated the common HPV 16, 18, 31, and 45 variants in Iran [19][20][21]. Regard to above-mentioned data that HPV 39 is one of the five most common HPV types in Iranian women with cervical cancer [14], this study aimed to investigate the frequent HPV 39 variants circulating in Iran.…”
Section: Introductionmentioning
confidence: 99%